How Evidence-Based Practice (E3BP) Informs Speech-Language Pathology for Primary Progressive Aphasia. (27th March 2020) - Ruggero, Leanne; Croot, Karen; Nickels, Lyndsey
Amelioration of communication impairment in primary progressive aphasia (PPA) is an area of clinical importance and current research. Speech-language pathologists (SLPs) have a range of skills and interventions to support communication in PPA; however, underrecognition of their role and low referral rates is an ongoing concern. The E 3 BP conceptualization of evidence-based practice comprises 3 components: research-based evidence, practice-based evidence, and informed patient preferences. Here, we will describe how evidence for managing the communication difficulties experienced by individuals with PPA exists at all 3 levels of the (E 3 BP) model, highlighting how this allows SLP interventions to be both evidence based and patient centered. We encourage health professionals to value and utilize the wide range of services that SLPs can offer when working with individuals with PPA, to educate, remediate everyday linguistic skills, increase daily participation, and maximize overall quality of life.